Effect of motions on the performance and mooring tension of a floating pontoon-type breakwater. (4th March 2022) - Huang, Guoxing; Sun, Zhenxiang; Song, Yue; Zhang, Ningchuan
ABSTRACT: This study experimentally investigated the performance and hydrodynamic response of a flexible floating pontoon-type breakwater. The floating breakwater consists of ten rubber pontoons with flexible connections. The effect of relative breadth and relative wave height on the wave transmission, reflection and dissipation coefficients has been discussed for various assembly configurations of the floating breakwater. The results show that the flexible multi-pontoon breakwater has better performance with larger relative breadth. The configuration of continuous pontoons without gap has the best performance on wave attenuation for relatively long waves. In short waves, however, better performance was observed on the pontoon configurations of two equal sets with gap. The novelty of this study is figuring out the relationship among the wave reflection coefficient, motion and mooring tension of the breakwater. The results reveal that the variation of reflection coefficient versus relative breadth shows the same trend as that of mooring tension.